ADVANCING TRANSITIONAL CARE FOR COMMUNITY-BASED ADULTS WITH STROKE AND MULTIPLE CHRONIC CONDITIONS. (11th November 2018) - Markle-Reid, M; Valaitis, R; Archer, N; Bartholomew, A; Fisher, K; Flek, R; Gafni, A; Ploeg, J
Abstract: To examine the feasibility and acceptability of a 6-month transitional care intervention linking outpatient rehabilitation and community-based care, and to explore its preliminary effects on patient and provider outcomes and health service use and costs for older adults with stroke and multiple chronic conditions. A mixed-methods study (QUAL + quant) was used to examine the feasibility of the intervention and to explore its effects on quality of life, self-efficacy, depression, anxiety and health service use and costs. The tailored 6-month stroke rehabilitation intervention was delivered by an interprofessional (IP) team and supported by a web-based app, 'My Stroke Care (MYST)'. Of the 30 participants, 60% had ≥ 6 chronic conditions, 47% had depressive symptoms, 13% had moderate to severe anxiety, and 54% were hospitalized for ≥16 days in the past 6 months. Preliminary findings suggest the intervention is feasible and acceptable to the IP team and older adult participants. Providers perceived the following benefits associated with the intervention: increased awareness and use of community resources, increased communication and coordination between inpatient and outpatient teams, increased use of stroke best practices, increased understanding of patients' needs, and increased focus on patient-oriented goals and strengths. Significant improvement was seen in patients' self-efficacy (p=0.04) and a reduction in hospitalizations (p< 0.0001) over the study period. The findings support the feasibility and preliminary effectiveness of the intervention in improving patient outcomes, building capacity among an outpatient rehabilitation team, and using MYST as a platform for information sharing and goal setting.